EFFECT OF TEMPERATURE AND LIGHT ON PHYTOCHEMICAL PROFILING AND ANTIMICROBIAL ACTIVITY OF ANDROGRAPHIS PANICULATA (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
Andrographis paniculata (Acanthaceae) is an annual herb. It is found in Sri Lanka, and throughout the plains of India especially Tamilnadu, Maharashtra, Karnataka, and Orissa. Various medicinal properties like cholevetic, antidiarrheal, immunostimulant and anti-inflammatory have been attributed to this plant in the traditional system of Indian medicine. Further reported activities are hepatoprotective, antimalarial, anticancer, antihypertensive, antipyretic, antithrombotic and antidote for snake bites. The present study aimed to evaluate the anti-microbial activity for the isopropanol extract of A. paniculata against different bacterial strains such as E. coli, K. pneumoniae, P. vulgaris, S. pneumoniae, P. aeruginosa, S. aureus by determining inhibitory concentration and zone of inhibition. Minimum inhibitory concentration and zone of inhibition values and the high bioactive metabolites production was observed in different extracts of A. paniculata under different physical stress (Light and temperatures). The results revealed that, the isopropanol extract of A. paniculata is potent for inhibiting bacterial growth and various secondary metabolites production in dark condition at 37°C than other tested parameters.